Management of childbearing with hypermobile Ehlers-Danlos syndrome and hypermobility spectrum disorders: A scoping review and expert co-creation of evidence-based clinical guidelines. - Sally Pezaro; Isabelle Brock; Maggie Buckley; Sarahann Callaway; Serwet Demirdas; Alan Hakim; Cheryl Harris; Carole High Gross; Megan Karanfil; Isabelle Le Ray; Laura McGillis; Bonnie Nasar; et al. (PLoS ONE)
Objective To co-create expert guidelines for the management of pregnancy, birth, and postpartum recovery in the context of hypermobile Ehlers-Danlos syndrome (hEDS) and hypermobility spectrum disorders (HSD). Design Scoping Review and Expert Co-creation. Setting United Kingdom, United States of America, Canada, France, Sweden, Luxembourg, Germany, Italy, and the Netherlands. Sample Co-creators (n = 15) included expertise from patients and clinicians from the International Consortium on the Ehlers-Danlos syndromes and Hypermobility Spectrum Disorders, facilitated by the Ehlers-Danlos Society. Methods A scoping review using Embase, Medline, the Cochrane Central Register of Controlled Trials and CINHAL was conducted from May 2022 to September 2023. Articles were included if they reported primary research findings in relation to childbearing with hEDS/HSD, including case reports. No language limitations were placed on our search, and our team had the ability to translate and screen articles retrieved in English, French, Spanish, Italian, Russian, Swedish, Norwegian, Dutch, Danish, German, and Portuguese. The Mixed Methods Appraisal Tool was used to assess bias and quality appraise articles selected. The co-creation of guidelines was based on descriptive evidence synthesis along with practical and clinical experience supported by patient and public involvement activities. Results Primary research studies (n = 14) and case studies (n = 21) including a total of 1,260,317 participants informed the co-creation of guidelines in four overarching categories: 1) Preconceptual: conception and screening, 2) Antenatal: risk assessment, management of miscarriage and termination of pregnancy, gastrointestinal issues and mobility, 3) Intrapartum: risk assessment, birth choices (mode of birth and intended place of birth), mobility in labor and anesthesia, and 4) Postpartum: wound healing, pelvic health, care of the newborn and infant feeding. Guidelines were also included in relation to pain management, mental health, nutrition and the common co-morbidities of postural orthostatic tachycardia syndrome, other forms of dysautonomia, and mast cell diseases. Conclusions There is limited high quality evidence available. Individualized strategies are proposed for the management of childbearing people with hEDS/HSD throughout pregnancy, birth, and the postpartum period. A multidisciplinary approach is advised to address frequently seen issues in this population such as tissue fragility, joint hypermobility, and pain, as well as common comorbidities, including dysautonomia and mast cell diseases.